Multidisciplinary Day Surgery Unit: a Health Technology Assessment. (30th September 2020) - Pietrantonio, M; Caracciolo, A; Barbarino, A; Triassi, M
Abstract: Issue: The aim of this study was to improve effectiveness, efficiency and quality of healthcare provided in Day Surgery (DS) setting at "Villa Malta" Hospital in Sarno (Italy). Health Technology Assessment (HTA) was used to compare two organisational models: the first one, in force at the beginning of the study, was characterized by a decentralisation of care activities at the individual Surgery Units; the other one provided for a centralisation of care activities in one unit, named the Multidisciplinary Day Surgery Unit (MDSU). Description of the Problem: We evaluated economical (cost-minimisation analysis), performance (effectiveness, efficiency, appropriateness, quality and safety) and ethical-social aspects. The cost-minimisation analysis took into account costs incurred and revenues received (DRG-based reimbursement). The perceived quality and the ethical and social impacts were assessed by reference to the voluntary interruption of pregnancy (VIP) and the increasing offer of the Otorhinolaryngology services. Results: MDSU has resulted in a net gain of €1, 261, 097 per year. This is a result of the increase in hospitalisation production of €1, 235, 869 and the savings on staff costs of €30, 476. The new model also shown an improvement in efficiency through standardisation of the number of DS admissions and in perceived quality concerning VIP, ensuring greater privacy and humanisation for the patients. Finally, the introduction of the Otorhinolaryngology services in DS has increased the quality of healthcare on offer, without the need to transfer the surgical candidates to other hospitals. Lessons: The centralised model has shown definite advantages over the decentralised one. MDSU was adopted to provide DS services at "Villa Malta" Hospital and this organisational model could be chosen by other hospitals to improve quality of healthcare. Key messages: MDSU has advantages especially in economic, ethical and social terms. MDSU increases hospitalisation production, improves humanisation of patients and increases quality of healthcare on offer.